The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2337/dc11-0495
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soy Germ Pasta Improves Endothelial Function, Blood Pressure, and Oxidative Stress in Patients With Type 2 Diabetes

Abstract: OBJECTIVETo compare the effects of a novel soy germ–enriched pasta, containing isoflavone aglycons, with conventional pasta on endothelial function and cardiovascular risk markers in patients with type 2 diabetes (T2D).RESEARCH DESIGN AND METHODSThis randomized controlled double-blind crossover study compared one serving/day of soy germ pasta and conventional pasta for 8 weeks for effects on brachial artery flow-mediated vasodilation, blood pressure, plasma lipids, oxidized LDL cholesterol, 8-iso-PGF2α, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 12 publications
0
35
0
1
Order By: Relevance
“…[39,40] We were not able to locate trials with T2D or CVD as outcome, but one study calculated the 10-year Framingham coronary heart disease (CHD) risk score. [40] • Third, 14 studies were identified where different types of pasta were compared, including 3 studies that compared whole grain to refined grain pasta, [46-48] 6 studies that compared fiber-fortified to non-fiber-fortified pasta, [49][50][51][52][53][54] 2 studies that compared soy pasta to conventional pasta, [55,56] and 3 studies that contrasted pasta made from an ancient wheat grain variety, the Khorasan wheat, to pasta made from regular durum or soft wheat. [57][58][59] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39,40] We were not able to locate trials with T2D or CVD as outcome, but one study calculated the 10-year Framingham coronary heart disease (CHD) risk score. [40] • Third, 14 studies were identified where different types of pasta were compared, including 3 studies that compared whole grain to refined grain pasta, [46-48] 6 studies that compared fiber-fortified to non-fiber-fortified pasta, [49][50][51][52][53][54] 2 studies that compared soy pasta to conventional pasta, [55,56] and 3 studies that contrasted pasta made from an ancient wheat grain variety, the Khorasan wheat, to pasta made from regular durum or soft wheat. [57][58][59] …”
Section: Resultsmentioning
confidence: 99%
“…In the two randomized controlled trials that compared soy germ pasta to conventional pasta, soy germ pasta enriched in isoflavone aglycons was found to reduce total and LDL cholesterol, and increase flow-mediated vasodilation more than conventional pasta in adults with hypercholesterolemia in 4 weeks, [55] and was also found to significantly reduce systolic and diastolic blood pressure, plasma homocysteine, and improved flowmediated vasodilation and plasma total antioxidant capacity in T2D patients after an 8-week intervention, [56] both in the virtual absence of soy protein.…”
Section: Soy Germ Vs Conventionalmentioning
confidence: 99%
“…Consumption of soy foods has been shown to have beneficial effects on various aspects of human health including reduced risk of inflammation-related diseases, such as cardiovascular disease (11,12), diabetes (13), and certain types of cancers (14,15). Soy and soy isoflavone have been shown to inhibit cell adhesion molecule expression in cultured endothelial cells (16,17), reduce production of proinflammatory cytokines, and decrease oxidative stress in animal models (18 -22).…”
Section: Introductionmentioning
confidence: 99%
“…10 Consumption of soy foods has been shown to have beneficial effects on multiple aspects of human health, including reduced risk of inflammation-related diseases, such as cardiovascular disease, diabetes, and certain cancers. 1116 It has been hypothesized that the anti-inflammatory and antioxidative activity of soy constituents might explain some of its health benefits. 1619 Studies have shown that soy and its isoflavones can inhibit cell adhesion molecule expression in cultured endothelial cells, 17,18 reduce production of proinflammatory cytokines, and decrease oxidative stress in animal models.…”
mentioning
confidence: 99%